2008
DOI: 10.1002/bit.21648
|View full text |Cite
|
Sign up to set email alerts
|

Optimized bone regeneration based on sustained release from three‐dimensional fibrous PLGA/HAp composite scaffolds loaded with BMP‐2

Abstract: Contemporary treatment of critical bone defect remains a significant challenge in the field of orthopedic surgery. Engineered biomaterials combined with growth factors have emerged as a new treatment alternative in bone repair and regeneration. Our approach is to encapsulate bone morphogenetic protein-2 (BMP-2) into a polymeric matrix in different ways and characterize their individual performance in a nude mouse model. The main objective of this study is to examine whether the PLGA/HAp composite fibrous scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 29 publications
5
96
0
1
Order By: Relevance
“…Hence HA has a strong capacity to absorb BMP-2. Studies by Fu et al 43 and Jeon et al 44 also showed that, after addition of HA, the ability of the material to facilitate sustained release of BMP-2 was significantly improved. This is consistent with our BMP-2 data.…”
Section: Discussionmentioning
confidence: 93%
“…Hence HA has a strong capacity to absorb BMP-2. Studies by Fu et al 43 and Jeon et al 44 also showed that, after addition of HA, the ability of the material to facilitate sustained release of BMP-2 was significantly improved. This is consistent with our BMP-2 data.…”
Section: Discussionmentioning
confidence: 93%
“…[39][40][41] However, BMP-2 tends to disperse rather than act locally when incorporated into the human body. Therefore, BMP-2 must be compounded with a carrier to control its release over an extended time period.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit femurs, a well-established model of bone tissue defects (Fu et al, 2008;Wu et al, 2010), were implanted with the composite biomaterials in this study.…”
Section: Discussionmentioning
confidence: 99%